(untitled) (Cambridge, UK, 2004)
Although Kantian autonomy is often considered independent of time and place, J.B. Schneewind's landmark study, The Invention of Autonomy, has shown that much can be learned by analyzing Kant's moral philosophy in the context of the history of modern moral philosophy. Distinguished contributors accordingly relate Kant's work to the historical context of his predecessors (as well as the empirical context of human agency) in this valuable resource for professionals and advanced students.
Keywords: Autonomy (Philosophy); History,Quyền tự chủ (triết học)